Inhibitory effect of Dolichos biflorus extract on allergic airway inflammation and hyperresponsiveness in animal model of ovalbumin-induced asthma - Anupama Ashok Suralkar; Sanjay B Kasture (International Journal of Phytomedicine, 2013)
The context: Bronchial asthma is an allergic disorder characterized by airway hyper- responsiveness, infiltration of various inflammatory mediators and remodeling of the airways. Asthma is triggered by various factors like drugs, respiratory infection, dust, cold air, exercise, emotions, occupational stimuli, chemicals, histamine, and ovalbumin. Traditional medicinal plants are commonly used to treat or prevent asthma and its causes. Purpose of the study: Traditionally seeds of Dolichos biflorus are used in the treatment of cough, edema and asthma. The present study was designed to evaluate inhibitory effect of Dolichos biflorus extract on allergic airway inflammation and hyperresponsiveness in animal model of ovalbumin-induced asthma. Main findings: With the treatment of ethanolic extract of Dolichos biflorus (DB) seeds, there was significant decrease in inflammatory cell count, level of nitric oxide and total protein in bronchoalveolar lavage (BAL) fluid at the oral dose of 100, 200 and 400 mg/kg. DB also restored the level of lung antioxidant enzymes (LPO, GSH, SOD, Catalase) and reduced the wet/dry weight ratio. In histopathological examination of lung tissue, DB protected the lungs from pathological changes induced by OVA. Summary: These results indicate that ethanolic extract of Dolichos biflorus seeds decreased allergic airway inflammation and hyperresponsiveness by decreasing the infiltration of inflammatory cells in the airway. Potential implications: Our data suggests usefulness of Dolichos biflorus in prophylaxis and management of asthma.